Is Fletcher's situationism Christian? - Götz, Ignacio L. (Scottish journal of theology, 1970)
The question whether or not Fletcher's situationism is truly a Christian ethics has been raised before. Fletcher himself tells us so at the beginning of his book Situation Ethics. According to him the accusation is that he fails to treat situation ethics within a theological framework. Fletcher's answer is that he does so on purpose, since the challenge of situationism does not ultimately depend upon one's theological or non-theological commitments.